2017
DOI: 10.1371/journal.pone.0169398
|View full text |Cite
|
Sign up to set email alerts
|

Citations for Randomized Controlled Trials in Sepsis Literature: The Halo Effect Caused by Journal Impact Factor

Abstract: Citations for randomized controlled trials (RCT) are important for the dissemination of study results. However, predictors of citations for RCTs have not been investigated. The study aimed to investigate the predictors of citations for RCTs in sepsis literature. RCTs that investigated the efficacy of treatment strategies on clinical outcomes in sepsis patients were included, and publication dates were restricted to the period from 2000 to 2016. Risk of bias was assessed using the Cochrane handbook for systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In addition, the eminence of scholars or the reputation of journals where the work is published can make a significant contribution to their burstness—this is called the halo effect (Small, 2004 ). In a recent paper, Zhang and Poucke ( 2017 ) showed that journal impact factor has a significant impact on the citations that a paper received. Another study by Antoniou et al ( 2015 , p. 286) identified “study design, studies reporting design in the title, long articles, and studies with high number of references” as predictors of higher citation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the eminence of scholars or the reputation of journals where the work is published can make a significant contribution to their burstness—this is called the halo effect (Small, 2004 ). In a recent paper, Zhang and Poucke ( 2017 ) showed that journal impact factor has a significant impact on the citations that a paper received. Another study by Antoniou et al ( 2015 , p. 286) identified “study design, studies reporting design in the title, long articles, and studies with high number of references” as predictors of higher citation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, timeliness of research contents has a different effect on different disciplines. For instance, scholars in some experimental disciplines prefer to cite younger scientific achievements (for example, biology and AI), whereas in contrast, in certain theoretical disciplines (for example, Mathematics), those existing literature studies that have been fully validated are more likely to be cited [12,15]. To this end, we consider employing a function to measure the relation between the effect to the probability of a paper to be cited by another paper in the same discipline and the paper age t, and the function can be expressed as the following form: Figure 3: Summary of the submission process.…”
Section: Modeling Of Citation Processmentioning
confidence: 99%
“…JIF is calculated via the number of references; thus, it could also be improved by increasing the number of references [12][13][14]. In [15], Zhang and Van Poucke suggested that journals with short publication delay tend to receive higher impact factors. Yu et al developed a transfer function model to simulate the distributed citation process [16].…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, large amount of citations in an individual's profile is often due to authoring innovative methodology reports, clinical trials, large cohort studies, systematic reviews, and practice recommendations. 66 67 68 A notable example is the case of Oliver H. Lowry, 69 who published his paper on protein measurement with the folin phenol reagent in 1951. As of February 10, 2018, Lowry's profile in Scopus records 261,840 total citations for 226 documents with 244,589 linked to the seminal methodology paper.…”
Section: Traditional Author Impact Metricsmentioning
confidence: 99%